Oxidation of 3,4-dihydroisoquinolinium salts with DMSO/conc HCl - Somsak Ruchirawat (2018)
3,4-Dihydroisoquinolinium salts can be oxidized to the corresponding isoquinolones by DMSO in conc HCl. © 1984.